PERTANGGUNGJAWABAN PIDANA BADAN USAHA BERBENTUK CV (COMMANDITAIRE VENNOOTSCHAP) DALAM PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Abdul Aziz Alsa; Ningrum Natasya Sirait; Mahmul Siregar; Muhammad Hamdan (USU LAW JOURNAL, 2015)
ABSTRACT Commanditaire Vennootschap (CV) is an uncorporated business entity as a perpetrators of enviromental crime is obliged to mantain the function of the enviroment and manage the pollutions or enviromental damages. Pollutions or enviromental damages caused by an economical contents and will be increase as the progress of economical. It is a duty of every person to mantain the functions of the enviroment and manages the pollutions or enviromental damages.The responsibility of an uncorporate business entity to enviromental protection and management may be convicted to the business entity , and also those who govern the enviromental crimes and people who lead the offense. The uncorporate responsibility in enviromental crime may be convicted to the association and to the agents that consist by general partner and limited partner on a duty that caused a pollutions and enviromental damages. Keyword: Responsibility, Corporate, Commanditaire Vennootschap, CV, Enviromental Protection and Management.